2014
DOI: 10.1590/1517-86922014200301879
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho em teste cardiopulmonar de adolescentes: peso normal e excesso de peso

Abstract: RESUMOIntrodução: Sabe-se que o excesso de peso interfere no desempenho físico do cotidiano do adolescente e, consequentemente, na aptidão física e na capacidade cardiorrespiratória. Objetivo: O estudo objetivou identificar e comparar os valores das variáveis cardiorrespiratórias no limiar anaeróbico ventilatório (LAV) de adolescentes com peso normal e excesso de peso. Métodos: A amostra foi composta por 140 adolescentes de ambos os sexos entre 10 e 14 anos, escolares do município de Vitória, ES, Brasil. Foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…On the other hand, Gomes et al (36) developed a study with 140 male and female adolescents between 10 and 14 years of age, divided in two groups, one with normal weight and the other overweight. The adolescents were submitted to a cardiopulmonary exercise test on an ergonometric treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Gomes et al (36) developed a study with 140 male and female adolescents between 10 and 14 years of age, divided in two groups, one with normal weight and the other overweight. The adolescents were submitted to a cardiopulmonary exercise test on an ergonometric treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…A national study compared the performance in the six-minute walk test applied to schoolchildren aged 8 to 10 years and found no significant difference among the eutrophic, overweight and obese groups, but found that the final heart rate of the test was significantly higher among overweight children (18) . Overweight adolescents also presented impairment in cardiorespiratory fitness at the maximum and submaximal levels compared to adolescents with normal weight (19) . In some cases, due to lack of information, family counseling and professional counseling, associated with the desire to lose weight for better physical performance or, for fear or fear of criticism and embarrassing jokes of colleagues and relatives, some children follow radical initiatives to control and reduce weight.…”
Section: Discussionmentioning
confidence: 94%
“…25 Em recente pesquisa, foi evidenciado que os adolescentes com excesso de peso apresentam prejuízo na aptidão cardiorrespiratória não somente ao nível máximo, mas também no submáximo, quando comparados aos adolescentes com peso normal. 26 Ao comparar crianças eutróficas sedentárias com obesas sedentárias, o estudo observou maior batimento cardíaco ao repouso e menor capacidade física por parte dos obesos. 27 As crianças obesas apresentam modificações na variabilidade da frequência cardíaca, caracterizada por redução da atividade simpática e parassimpática.…”
Section: Discussionunclassified